Effects of dietary Nutrafito Plus on growth, haemotological parameters and total ammonia‐nitrogen excretion of juvenile striped catfish Pangasianodon hypophthalmus. (18th December 2014) - Güroy, Betül; Mantoğlu, Serhan; Merrifield, Daniel Lee; Guroy, Derya
Abstract: A feeding trial was performed to determine the effect of a commercial source of Yucca schidigera and Quillaja saponaria extracts (Nutrafito Plus ® ), in practical diets, on striped catfish Pangasianodon hypophthalmus growth, feed utilization, body composition, total ammonia‐nitrogen (TAN) excretion and haematological parameters. Four experimental diets were supplemented with Nutrafito Plus ® at 0%, 0.01%, 0.02% and 0.03% (diets: control, N01, N02 and N03 respectively). Three replicate groups of striped catfish, with initial mean weight of 1.78 ± 0.05 g, were fed one of the four diets for 12 weeks. The specific growth rate (SGR) and final weight of fish fed diet N03 was significantly higher ( P < 0.05) than fish fed the other dietary treatments. The growth performance of fish fed diets N01 and N02 were not significantly different compared to fish fed the control diet. Striped catfish fed diet N03 had improved feed conversion ratio (FCR), net protein utilization (NPU) and protein efficiency ratio (PER) than the control ( P < 0.05). The inclusion of the high dietary level of Yucca schidigera and Quillaja saponaria, diet N03, reduced TAN compared to all groups. Dietary inclusion of Yucca schidigera and Quillaja saponaria at all levels investigated did not affect the whole body proximate composition of the striped catfish ( P > 0.05). The packed cell volume (PCV) and haemoglobin level in fish fed diet N03 was significantly higher than in the fish fed the control diet. The present study demonstrates that dietary inclusion of Yucca schidigera and Quillaja saponaria induced positive effects on growth performance and haematological parameters and decreased TAN excretion in striped catfish.